PRODUKSI SIARAN LANGSUNG TVONE BIRO MAKASSAR DALAM PROGRAM APA KABAR INDONESIA PAGI EDISI SEPTEMBER 2019 (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
This study examines the process of producing live broadcasts (live report). The aim is to find out the stages of the live broadcast production process (live report) and further describe related factors inhibiting live broadcast production (live report) tvOne Makassar bureau. The informants in this study were the head of the Makassar TVOne Bureau, the coverage coordinator as well as the program producer, Reporter, Cameraman and Program Director. The results of the research showed the live broadcast production process of the TVOne Makassar Bureau through three stages, firstly pre-production, secondly the production process, and the third, post-production.This study examines the process of producing live broadcasts (live report). The aim is to find out the stages of the live broadcast production process (live report) and further describe related factors inhibiting live broadcast production (live report) tvOne Makassar bureau. The informants in this study were the head of the Makassar TVOne Bureau, the coverage coordinator as well as the program producer, Reporter, Cameraman and Program Director. The results of the research showed the live broadcast production process of the TVOne Makassar Bureau through three stages, firstly pre-production, secondly the production process, and the third, post-production.